The effects of prenatal multiple micronutrient supplementation and small-quantity lipid-based nutrient supplementation on small vulnerable newborn types in low-income and middle-income countries: A meta-analysis of individual participant data - Wang, Dongqing; Liu, Enju; Perumal, Nandita; Partap, Uttara; Cliffer, Ilana R.; Costa, Janaína Calu; Wang, Molin; Fawzi, Wafaie W.; Adu-Afarwuah, Seth; Ashorn, Per; Ashorn, Ulla; Mridha, Malay Kanti; et al. (Elsevier, 2025)
Background Small vulnerable newborn types, defined by combinations of being born too soon or too small, have distinct determinants and health consequences. We aimed to assess the effects of prenatal multiple micronutrient supplementation (MMS) and small-quantity lipid-based nutrient supplementation (SQ-LNS) on small vulnerable newborn types, which are currently unknown. Methods In this meta-analysis, individual participant data from randomised controlled trials of MMS and randomised controlled trials of SQ-LNS in low-income and middle-income countries were used. We systematically searched the literature using PubMed, Embase, and Web of Science to identify randomised controlled trials of prenatal nutritional supplementation using MMS or SQ-LNS among pregnant people published between Jan 1, 2000, and Dec 31, 2021. Studies were excluded if they were conducted exclusively among participants selected by pre-existing health conditions, such as anaemia status, HIV infection, or diabetes. We contacted the corresponding authors of all identified studies to seek data contribution. As individual participant data became available, we mapped relevant variables and harmonised the data across studies. Iron and folic acid supplementation was the control group in most studies. Newborns were classified into ten groups through the combinations of preterm or term birth, small, appropriate, and large for gestational age, and low birthweight (LBW) or non-LBW. Newborns were also analysed using a four-group categorisation of preterm or term and LBW or non-LBW. Log-binomial models were used to estimate study-specific risk ratios (RRs), which were pooled using meta-analyses. Findings 14 randomised controlled trials of MMS (n=42 618; the mean maternal age at study enrolment was 24·3 years [SD 5.6]; 22 086 [51·8%] male neonates and 20 532 [48·2%] female neonates) and four randomised controlled trials of SQ-LNS (n=6246; the mean maternal age at study enrolment was 23·3 years [SD 5·3]; 3137 [50·2%] male neonates and 3109 [49·8%] female neonates) were used. In the ten-group categorisation of small vulnerable newborns, prenatal MMS reduced the risk of preterm–small for gestational age (SGA)–LBW (RR 0·73, 95% CI 0·64–0·84; p=0·0003); preterm–appropriate for gestational age (AGA)–LBW (0·82, 0·74–0·91; p=0·0010); preterm–AGA–non-LBW (0·89, 0·80–0·98; p=0·019); term–SGA–LBW (0·91, 0·85–0·96; p=0·0046); and term–SGA–non-LBW (0·95, 0·90–1·00; p=0·050). In the four-group categorisation, prenatal MMS reduced the risk of preterm–SGA (0·71, 0·62–0·82; p=0·0002) and term–SGA (0·93, 0·89–0·98; p=0·0066). Prenatal SQ-LNS had no significant effects on the risk of giving birth to small vulnerable newborns except for preterm–large for gestational age–non-LBW in the ten-group categorisation (0·78, 0·65–0·94; p=0·023). Interpretation Prenatal MMS and SQ-LNS reduce the risk of giving birth to small vulnerable newborns to varying extents, with the greatest magnitude of effects observed for small vulnerable newborn types that confer the greatest neonatal mortality risk. This study underscores the importance of nutritional supplements in prenatal care.